LEADERSHIP STYLE OF NGO’S CONTRIBUTION TO GENDER AND SUSTAINABLE ENVIRONMENT DEVELOPMENT IN YOGYAKARTA PROVINCE OF INDONESIA - Shanta Sheema Akhter (LPPM UNY, 2015)
The main purpose of this study was to determine kind of leadership style used in the selected NGOs in Yogyakarta province in Indonesia and to analyze the optimal contributions of gender and sustainable environment development of their NGOs of Yogyakarta province in Indonesia. Qualitative research case study method was used to analyze this study. Data was collected by documentation, direct observations and interview. Sample was selected from two NGOs purposively: WALHI Yogyakarta and Mitra Pranata. The subjects of this study were the leaders, staffs and members of Mitra pranata and WALHI Yogyakarta NGO in Yogyakarta in Indonesia. Data was collected from two NGO leaders, from all staffs and selected members. The results showed that these NGO’s leader used Transformational leadership style. WALHI Yogyakarta NGO has good achievements for Yogyakarta environment including- forest, spring, mine and others because they work about three aspects -policy research, campaign and organizing community. Mitra Pranata NGO also has good achievements. They work in small areas in Lendah village, Kulon Progo